Про тебя самого: справочное издание / А. А. Дорохов - Дорохов Алексей Алексеевич (Детская литература, 1989)
Экземпляры: (20200304) / Инвентарный номер: 19807 / Цена: / Сис.шифр: 28.7 / Авт.знак: Д 69 / ББК: 28.706